Community Service: Communication in Digital Era: Business Presentations and Their Relevance in the Workplace - Hidayat, Vinny Stephanie; Carolina, Verani; Handayani, Rini; Kambono, Herman; Wijaya, I Nyoman Agus; Setiana, Sinta; Tan , Kwang En; Surifran, Vicky Putra (Universitas Mathla'ul Anwar Banten, 2024)
For GJKI Andir Bandung members, a community service event with the topic